The relationship between high-density residential and mental health / Marlyana Azyyati Marzukhi ... [et al.] - Marzukhi, Marlyana Azyyati; Abdullah, Yusfida Ayu; Ghazali, Nur Masyitah; Ling, Oliver Hoon Leh; Ahmad Zaki, Zulkifli; Yusup, Mohammad; Danial, Muhammad Hakim (College of Built Environment, 2023)
high-density residential is highly associated with urbanization trends. As people move to urban areas for job opportunities and better lifestyles, it causes an increase in urban population numbers.